Application and theory of petri nets and concurrency : 37th International Conference, PETRI NETS 2016, Toruń, Poland, June 19-24, 2016. Proceedings /: 37th International Conference, PETRI NETS 2016, Toruń, Poland, June 19-24, 2016. Proceedings. (2016) - Unknown
No abstract available